Efeitos da pandemia do Covid-19 na qualidade dos itens retornados: um estudo de caso em uma empresa de bebidas - Fonseca, Marina Luz (Universidade Federal de São Carlos, 2021)
With the COVID-19 pandemic, which arrived in Brazil in mid-February 2020, the country has been going through a major health crisis and has been facing structural and economic problems that affected - and continues to affect - companies from different segments, not differing from companies in the food sector, including the beverages industries. With bars and restaurants with intermittent operation, several containers that should have returned to the factories, suffered degradation due to the time spent in the market, a fact that negatively affects the turnover indicator and the quality of the packaging in question. Given the circumstances, this paper, analyzes the role of reverse logistics and the quality of returnable packaging of a beverage company in the face of a pandemic, in comparison with the non-pandemic scenario. The study addresses the improvement of the reverse channels of returnable 1L containers in an atypical context, which has variations in the volume and worsens in returned containers quality, which is highly desirable in terms of sustainability and economy for companies. The results reveal that the closing of commercial establishments during the critical months of the pandemic in 2020 and 2021 affected the quality of working assets and harmed the Reverse Logistics process, in operational terms, for the company. Thus, the research contributed by bringing several challenges and lessons learned by the company during the pandemic, which resulted in optimizations in the RL process. In addition, it was important to observe how working with returnable packaging with quality is extremely relevant, resulting in reduced costs for the company, reducing the need to exploit resources for the production of new packaging and guaranteeing the safety of the final consumer.
The Covid-19 pandemic and its effects on the quality of returned items: a case study at a beverage company
Keywords: Logística reversa; Bebidas; Embalagens retornáveis; Qualidade; Covid-19; Sustentabilidade; Reverse Logistics; Beverages; Returnable Packaging; Quality; Sustainability; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO